Draw! - Solga, Kim. (Danbury, CT Grolier Educational Corporation, 1993)
Encourages readers to develop drawing skills through projects designed to teach basic principles of artistic technique and use of materials.
For ages 6-11.
Keywords: Drawing -- Technique -- Juvenile literature